Sedimentation study, Environmental Monitoring and Operations Guidance System (EMOGS), Kings Bay, Georgia and Florida : Phase III--FY 1989 - Aubrey, David G.; McSherry, T. R.; Spencer, Wayne D. (Woods Hole Oceanographic Institution, 1990)
Repeated side-scan sonar and multi-frequency bathymetric surveys, accompanied by accurate, high resolution, and repeatable navigation, were conducted in the vicinity of a tidal inlet to define the length and time scales associated with bedforms and channel shoaling in a structured tidal inlet. The study site, St. Mary's entrance channel along the Georgia/Florida border (Fig. I), has a dredged channel approximately 46-52 feet in depth, bordered by a large ebb tidal delta. The tidal inlet serves Cumberland Sound, Kings Bay, and associated waterways, providing a large discharge of water from the inlet that creates bedforms and channel shoaling, given the abundance of sand-sized sediment in the vicinity. The jettied inlet produces flows tht are predominately tidally-driven, whereas farther offshore the driving forces consist predominately of waves and storm-generated flows. In the channel reaches (Table 1) between these two areas, combined wave-steady flows are present, creating a myriad of scales of bedforms and shoaling patterns. This study was designed to elucidate the time and space scales of these variable bedforms and shoaling patterns, emphasizing the difference in these scales between the three different flow regimes. The results provide an important data base for quantifying shoaling processes and mechanisms in tidal inlet channels. Funding was provided by the National Oceanic Atmospheric Administration under Sea Grant No. NA860A-D-SG090.